Birth preparedness and related factors: a cross-sectional study in Tanzania City area - Yoko Shimpuku; Beatrice Mwilike; Keiko Ito; Dorkasi Mwakawanga; Naoki Hirose; Kazumi Kubota (BMC, 2021)
Abstract Background Birth preparedness could be the key factor that influences the choice of birthplace with skilled birth attendants. To reduce the high maternal mortality of Tanzania, a large study was planned to develop a smartphone app to promote birth preparedness in a city area of Tanzania. This study aimed to identify factors that influence birth preparedness in the city area of Tanzania. Methods Pregnant women were asked to complete the Birth Preparedness Questionnaire during antenatal visits using tablets. Multiple linear regression analyses were performed to determine the sociodemographic and obstetric characteristics that influenced the factors. Results A total of 211 participants were included in the analysis. Distance from the nearest health facility negatively influenced the total score of the Birth Preparedness Assessment (β= 0.7, p = 0.02). Education higher than college positively influenced the total score (β = 4.76, p = 0.01). Decision-making of birthplace by other people (not women) negatively influenced Family Support (β=1.18, p = 0.03). Having jobs negatively influenced Preparation of Money and Food (β=-1.02, p < 0.01) and positively influenced the knowledge (β = 0.75, p = 0.03). Being single positively influenced Preparation of Money and Food (β = 0.35, p = 0.19) and Preference of Skilled Birth Attendants (β = 0.42, p = 0.04). Experience of losing a baby negatively influenced the knowledge (β=0.80, p < 0.01) and Preference of Skilled Birth Attendants (β=0.38, p = 0.02). Conclusions The findings showed an updated information on pregnant Tanzanian women living in an urban area where rapid environmental development was observed. Birth preparedness was negatively affected when women reside far from the health facilities, the birthplace decision-making was taken by others beside the women, women have jobs, and when women have experienced the loss of a baby. We hope to use the information from this study as content in our future study, in which we will be applying a smartphone app intervention for healthy pregnancy and birth preparedness. This information will also help in guiding the analysis of this future study. Although generalization of the study needs careful consideration, it is important to reconsider issues surrounding birth preparedness as women's roles both in the family and society, are more, especially in urban settings.